Implementasi Peraturan Daerah N0mor 2 Tahun 2015 terhadap Pedagang Kaki Lima Kendaraan Bermobil di Kota Denpasar Selama Pandemi Covid-19 - Ayu Yuliany Adisti; Ida Ayu Putu Widiati; Luh Putu Suryani (Warmadewa Press, 2021)
Since the Covid-19 pandemic, many people have become street vendors in cars and park their vehicles on the side of the road. This violates the Denpasar City Regional Regulation Number 2 of 2015, therefore this study aims to examine the implementation of the Denpasar City Regulation Number 2 of 2015 concerning Street Vendors (PKL) for Mobile Vehicles and discuss the supervision of the PKL policy for motorized vehicles during the Covid-19 pandemic 19. The empirical research method based on the data obtained is from the results of observations, interviews, and documentation. Then the results of the data relevant to the formulation of the problem in this study were analyzed qualitatively and explained descriptively. From the results of the research conducted, it shows that the implementation of the policy of Street Vendors in Denpasar City cannot be carried out properly in accordance with the Denpasar City Regional Regulation Number 2 of 2015 due to the current pandemic situation and conditions which have resulted in many people being sent home and fired from their workplaces. forced to become a car dealer for daily income. The obstacle faced by the government in supervising street vendors is that it is difficult to register and appeal to them because it is easy to move from one place to another.